Proceso de control de crédito y su efecto en el grado de liquidez de banecuador sucursal Santo Domingo, Primer Semestre del Año 2016. - Garófalo Jiménez, Ana Johanna (2016)
Banco BanEcuador BCE B.P. Is a Financial Institution of the public sector that has been formed to contribute to the development of small and large producers of the country, and specifically in the province of Santo Domingo de los Tsáchilas. Therefore, the present investigation entitled "Credit control process and its effect on the degree of liquidity of Banco BanEcuador BCE BP Sucursal Santo Domingo, first half of 2016", was carried out with the purpose of analyzing the current situation regarding the controls Of credit granted to the clients and the processes that are carried out for the purpose. The objective of this study was to evaluate the effect of credit control processes on the degree of liquidity of Banecuador Sucursaal Santo Domingo, first half of 2016. In recent months, the financial institution's participation in the economy Of the productive sectors has increased significantly, however, this in turn showed a problem that, although it seems smaller, is of great importance as the weak application of credit policies. This problem leads to an increase in delinquency rates, thus distorting the credit culture of BanEcuador users. Given the situation, it is necessary to urgently implement not only credit policies, but also specific procedures, or protocols of action for the placement and recovery of loans, in order to reduce the high loan portfolio rates. The effects of the policies are not favorable to the Bank, since they lack efficiency, which is why the NPL ratio is 11.26% at the end of the first half of 2016, while the amount of past due loans is Of $640,177.79. Furthermore, there is no evidence of a regulation for the recovery process of this portfolio. On the other hand, the financial indicators showed a slickness of $0.18 to respond to the immediate demand of their depositors and a solvency of $0.43.